Determining The Theme For Architectural Design Of Tourist Accommodation Based On Big Data In The Canggu Village Area, Badung, Bali - Widanan, I Wayan; Prabawa, Made Suryanatha; Wiguna, Made Mas Surya (Politeknik Internasional Bali, 2024)
Canggu Village is the area in the Badung Regency, Bali, which has recently grown to be one of the main attractions for tourists. Accordingly, this region has undergone rapid development and an increase in tourism-oriented facilities. Unfortunately, not all of these facilities have been built with architectural themes related either to the demands of the market or to the Canggu or Bali Villages' local characteristics. On the other hand, information technologies have reached a point where much data, popularly known as Big Data, is constantly available and can be analyzed for any purpose. Such inconsistency in the architectural themes expressed with the availability of Big Data has presented the possibility of determining what architectural theme fits the tourism market in Canggu Village. The objective of this research is to establish the more exact architectural design theme for tourist accommodation in Canggu Village based on Big Data analysis, while maintaining respect for local architecture value, form, and norm. The quantitative approach in research is adopted during this research. In this case, it means data was collected through Big Data exploration. Further, the analysis was done using the comparative-correlational method. Data revealed that the highest ratio falls into Modern minimalist architecture, followed by modern Balinese architecture. It means the application of such themes in the Canggu Village area is concerned with Modern Minimalist Architecture and Modern Balinese Architecture. In the future, consideration must be given towards including both themes to maintain the local identity of the architecture in Canggu Village.